If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -2) = 5 + -1(4x + -17) Reorder the terms: 3(-2 + x) = 5 + -1(4x + -17) (-2 * 3 + x * 3) = 5 + -1(4x + -17) (-6 + 3x) = 5 + -1(4x + -17) Reorder the terms: -6 + 3x = 5 + -1(-17 + 4x) -6 + 3x = 5 + (-17 * -1 + 4x * -1) -6 + 3x = 5 + (17 + -4x) Combine like terms: 5 + 17 = 22 -6 + 3x = 22 + -4x Solving -6 + 3x = 22 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -6 + 3x + 4x = 22 + -4x + 4x Combine like terms: 3x + 4x = 7x -6 + 7x = 22 + -4x + 4x Combine like terms: -4x + 4x = 0 -6 + 7x = 22 + 0 -6 + 7x = 22 Add '6' to each side of the equation. -6 + 6 + 7x = 22 + 6 Combine like terms: -6 + 6 = 0 0 + 7x = 22 + 6 7x = 22 + 6 Combine like terms: 22 + 6 = 28 7x = 28 Divide each side by '7'. x = 4 Simplifying x = 4
| 5(3x-8)-2=5(x-4)+28 | | -5sin(x)+3cos(x)-1=0 | | 4.7(x-7)=-0.3x+20.6 | | 2x+6=9-3x | | 4x+6y=1380 | | X+13y=13 | | 4x+6y=1389 | | y=0.167x+2.443 | | 4/3y=16/60 | | y=1/2d1d2 | | -36=-4w+8(w-4) | | 6x+4+x=3x+4 | | 3(x+9)=9X+4-6x+23 | | 2(3x+4)-x+6=5x-2(x+1)+5 | | -2100x^3+1100x^2+1400x-400=0 | | -18=-6y+2(y+5) | | 2x+10+2x=x+16 | | b+18+3=74 | | 2x+4=65 | | -7v+4(v-4)=-13 | | 8x-4=4x+8x+2 | | 32=2/5(15p-10) | | y=1.6x+9.1 | | 2y=12x+16 | | -3x=x/5 | | 12v^7-32v^4/4v^3 | | x*1-y-7=0 | | 7(x+3)+3(x+3)=5x-5 | | 2.5=a/.5 | | 6y+17=37-10 | | 4v^2+4v=6 | | (4b-4)(b+6)= |